Misleading Germ Cell Phenotype in Pulmonary NUT Carcinoma Harboring the ZNF532-NUTM1 Fusion. (7th July 2021) - Agaimy, Abbas; Haller, Florian; Renner, André; Niedermeyer, Jost; Hartmann, Arndt; French, Christopher A.
Abstract : NUT carcinoma (aka NUT midline carcinoma) is a rare, still significantly underrecognized aggressive malignancy. Although historically considered a midline malignancy of children and young adults, NUT carcinoma can originate in almost any body site and in any age group. Beside the classic BRD4-NUTM1 fusion, less common fusion partners include BRD3, NSD3, ZNF532, and ZNF592 . Other fusions, including CIC, MGA, MXD4, MXD1, and BCORL1 are associated with sarcomas or cancers of unknown histogenesis. Involvement of the Z4 zinc finger protein (ZNF) family members ZNF532 and ZNF592 is exceedingly rare with only 3 recently reported cases. We herein describe a ZNF532-NUTM1 –rearranged NUT carcinoma presenting as a 7.5 cm mass in the left lower lung lobe of a 65-year-old woman. Histology revealed undifferentiated monotonous small round cells with focal epithelioid and rhabdoid elements within a variably myxoid stroma. Immunohistochemistry revealed paucity of keratins and variable p63 combined with extensive CD30 and PLAP expression, leading to initial diagnoses of combined small cell carcinoma, CD30-positive unclassified hematolymphoid malignancy and malignant germ cell neoplasm. Negativity for other more specific germ cell markers justified seeking a fourth opinion, which revealed diffuse expression of the NUT antibody. The diagnosis was then confirmed by fluorescence in situ hybridization. Targeted RNA sequencing revealed the ZNF532-NUTM1 fusion. Screening of 7 NUT carcinomas (5 with BRD4 - NUTM1 and 2 with NSD3-NUTM1 fusions) for germ cell markers revealed focal SALL4 reactivity in 3 cases (combined with variable AFP expression in 2), but none expressed CD30 or PLAP. An aberrant germ cell immunophenotype should be considered in NUT carcinoma to avoid misinterpretation as genuine germ cell malignancy as both diseases predominantly affect the young population, frequently involve the mediastinum and can be associated with elevated serum AFP.